2020
DOI: 10.1002/emp2.12211
|View full text |Cite
|
Sign up to set email alerts
|

Reducing infant catheterization in the emergency department through clean‐catch urine collection

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Diviney et al also proposed clean‐catch sampling as the preferred method, because the contamination rate was comparable to invasive methods 26 . Other studies found contamination rates of clean‐catch between 4.5% and 27%, 27–34 whereas Herreros et al 22 reported a contamination rate of 5%. In addition, the proportion of contamination can be influenced by the criteria used to define contamination, the person performing urine collection, techniques used to reduce contamination or stimulate urination, patient characteristics and setting.…”
Section: Discussionmentioning
confidence: 99%
“…Diviney et al also proposed clean‐catch sampling as the preferred method, because the contamination rate was comparable to invasive methods 26 . Other studies found contamination rates of clean‐catch between 4.5% and 27%, 27–34 whereas Herreros et al 22 reported a contamination rate of 5%. In addition, the proportion of contamination can be influenced by the criteria used to define contamination, the person performing urine collection, techniques used to reduce contamination or stimulate urination, patient characteristics and setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of invasive techniques to collect urine for urobiome research in the pediatric population raises an ethical concern. It is worth underlining that urine cultures of clean-catch urine samples have good efficacy in diagnosing urinary tract infections in children [ 20 , 21 ], and the contamination rate of urine collected via urethral catheterization is lower but not significantly different from that of clean-catch [ 21 ]. Interestingly, Bundgaard-Nielsen et al, who investigated the impact of the collection method on the urobiome composition, did not report any interpersonal daily or day-to-day deviations in microbiota composition in women, girls, or boys [ 22 ].…”
Section: The Urobiome Investigationmentioning
confidence: 99%
“…On this basis, the different international clinical practice guidelines have recommended the collection of urine cultures by CCUC, UC or suprapubic aspiration to establish a diagnosis of UTI, and UB is not considered as a valid method. [18][19][20]25,26 Sample contamination rates have been described to be between 4.5% and 39% for CCUC 5,6,[10][11][12]23,27,28 and between 1.6% and 14.3% for UC. 5,[10][11][12]23,[28][29][30] Labrosse et al found no significant differences in the contamination of samples obtained by CCUC and UC in infants younger than six months of age.…”
mentioning
confidence: 99%
“…[18][19][20]25,26 Sample contamination rates have been described to be between 4.5% and 39% for CCUC 5,6,[10][11][12]23,27,28 and between 1.6% and 14.3% for UC. 5,[10][11][12]23,[28][29][30] Labrosse et al found no significant differences in the contamination of samples obtained by CCUC and UC in infants younger than six months of age. 12 By contrast other studies found a significant difference in contamination between the two methods in paired samples.…”
mentioning
confidence: 99%